“Uisibilis in homine et contrectabilis Deus” (De Trinitate IV 42). Un análisis de la presencia de Cristo en el Antiguo Testamento en las obras de Hilario de Poitiers a la luz de la polémica antiarriana del s. IV - Alba López, Almudena (Vox Patrum, 2022)
The analysis of Old Testament theophanies was particularly important to Hilary of Poitiers, both in what regards the doctrinal development of his soteriological and Christological thought and in what concerns his struggle against those who denied the equality of the Father and the Son. Throughout this paper I will analyse the Gallic bishop’s cross-sectional analysis of the main theophanies witnessed by the prophets and patriarchs in the light of their future orientation in his works, mainly in De Trinitate and the Tractatus super psalmos. Hilary believed that the reason behind divine manifestations was none other than the annunciation of the new economy which was inaugurated with the Incarnation and to arouse the faith and hope required to await this moment and to be able to identify the Son in the carnal habitus he assumed in his coming within mankind. In order to differentiate theophanies from the incarnation, Hilary of Poitiers establishes a fundamental difference between the species creatae assumed by the Word in the theophanies and the assumption of the flesh in the Incarnation which is essential to understand the mysteries the purpose of the Son's mission, namely, the salvation of humankind.